Strain Elastography as a Valuable Diagnosis Tool in Intermediate Cytology (Bethesda III) Thyroid Nodules - Stoian, Dana; Borcan, Florin; Petre, Izabella; Mozos, Ioana; Varcus, Flore; Ivan, Viviana; Cioca, Andreea; Apostol, Adrian; Dehelean, Cristina Adriana (Diagnostics (Basel), 2019)
Fine needle aspiration (FNA) is considered the gold standard in the diagnostic of thyroid nodules. Using the recommended BETHESDA reporting system, up to 20% of results are classified as intermediate cytology. As there is no consensus whether ultrasound evaluation, lobectomy or surgery is the best treatment option, intermediate cytology results are considered a grey zone of the FNA. The main aim of our study was to evaluate the performance of combined advanced ultrasound techniques in the process of diagnosis and evaluation of the intermediate cytology cases after FNA. We evaluated 54 consecutive cases with intermediate cytology on FNA, using conventional B-mode ultrasound (2B), and strain elastography, using a linear multifrequency 6–13 MHz linear probe (Hitachi Prerius Machine, Hitachi Inc, Japan). All nodules were classified with our Thyroid Imaging Report and Data System (TI-RADS) proposed model, considering: vertical appearance, with antero-posterior diameter bigger than the transvers diameter, the so called taller than wide shape, irregular borders, intranodular inhomogeneity, marked hypoecogenicity, micro calcifications, the presence of suspect lymph nodes, and increased stiffness as suspicious for malignancy. The classification outcomes were compared with the pathology results, considered the gold standard diagnosis. The prevalence of cancer was 28.8%, with 13/45 cases having a clear diagnostic of cancer. Six cases were diagnosed with borderline follicular neoplasia, a category with unclear evolution, also considered as malignant in the analysis of the imaging results. In total, 16/19 cancer cases had increased stiffness on elastography. The cancer prevalence increased with TI-RADS category, being 25% in TI-RADS 4b category and 92.8% in TI-RADS 5 category. The AUROC (Area Under Receiver Operating Curve) of elastography alone, in differentiation of malignant thyroid nodules was 74.9%; the combination of elastographic and conventional ultrasound characteristics generated an even better AUROC, of 84.5%. The combined conventional ultrasound and elastography identified thyroid cancer in cases with intermediate cytology with a sensitivity of 89.5% with a specificity of 50%. High risk thyroid nodules, identified by combined high risk conventional ultrasound characteristics and increased stiffness, on strain elastography, are highly predictive for malignancy, in the intermediate cytology cases.